Denitration catalyst reclaimed material recycling method
By physically crushing the denitrification catalyst, soaking the hydrochloric acid solution, reacting the ammonium sulfate solution and calcining at high temperature, the problem of difficult removal of potassium and arsenic in the recovery material in the prior art is solved, and the recovery of catalyst activity and performance improvement is achieved.
Patent Information
- Application Number
- CN202411758778.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
AI Technical Summary
The existing denitrification catalyst recovery process is difficult to effectively remove potassium and arsenic from the recovered materials, resulting in unstable performance of the regeneration catalyst and poor activity recovery.
Physical pulverization and 16 mesh screening were used, followed by soaking with a hydrochloric acid solution of 4-8%, then an ammonium sulfate solution with a mass fraction of 8-12% was added to the rotary reactor for reaction, and finally high-temperature calcination was carried out under an inert gas atmosphere to activate the catalyst activity.
The potassium and arsenic in the denitrification catalyst are effectively removed, the activity of the catalyst is restored, and the performance and service life of the catalyst are improved.
Smart Images

Figure BDA0005167037050000071 
Figure BDA0005167037050000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of denitration catalysts, and more specifically, to a method for recycling denitration catalyst recovery materials. Background Art
[0002] Denitrification catalysts are widely used in flue gas treatment projects and are replaced after long-term operation due to decreased activity. At present, the treatment methods for waste denitrification catalysts mainly include landfill, incineration and recycling, among which recycling is valued for its resource conservation and environmental value. However, in the actual recycling process, the performance and service life of the regenerated catalyst are seriously affected due to the presence of a certain amount of harmful elements such as potassium and arsenic in the recycled material.
[0003] The existing denitrification catalyst recovery process is difficult to effectively remove potassium and arsenic from the recycled material, resulting in unstable performance of the regenerated catalyst and poor activity recovery. Although common physical screening and chemical washing methods can remove potassium and arsenic to a certain extent, they are inefficient, costly, and easily introduce new pollution sources, which is not conducive to large-scale promotion and application. Summary of the invention
[0004] In order to effectively reduce potassium and arsenic in recycled materials, the present application provides a method for recycling recycled denitration catalyst materials.
[0005] A method for recycling denitration catalyst recovery material comprises the following steps: (1) Pretreatment: crush the denitration catalyst recovery material and pass it through a 16-mesh sieve; (2) Cleaning: Soak the powder in a 4-8% hydrochloric acid solution for 11-12 hours, and rinse with water until neutral; (3) Purification: Place the washed recycled material in a rotary reactor, add 8-12% ammonium sulfate solution by mass, control the reaction temperature at 60-70°C, stir at 190-210 rpm, and continue for 2-2.2 hours; (4) Regeneration: The purified recycled material is dried and then calcined at 500-600°C in an inert gas atmosphere for 3.5-4 hours.
[0006] By adopting the above technical scheme, the denitration catalyst is physically crushed, which is beneficial to increase the contact area between the denitration catalyst and the solution in the subsequent treatment process, thereby removing impurities and potassium and arsenic on the surface of the denitration catalyst. Soaking in hydrochloric acid solution can preliminarily remove impurities on the surface of the denitration catalyst, which is beneficial to the contact between the denitration catalyst and the ammonium sulfate solution. Soaking in ammonium sulfate solution can effectively remove potassium and arsenic in the denitration catalyst. The purified catalyst is activated by high-temperature calcination, so that the catalytic activity of the catalyst is restored.
[0007] Preferably, the concentration of the hydrochloric acid solution is 5wt%, the concentration of the sodium sulfate solution is 10wt%, the calcination temperature is 550°C, and the duration is 3.5h.
[0008] By adopting the above technical scheme, the concentrations of hydrochloric acid solution and sodium sulfate solution are further optimized, so that impurities and potassium arsenic on the surface of the recycled material can be effectively removed and dissolved in the solution. The calcination temperature of 550°C can shorten the calcination time. Without reducing the activity of the catalyst, the calcination time is shortened and energy loss is reduced.
[0009] Preferably, in the purification step, ultrasonic assisted treatment is used, and the ultrasonic frequency is 240-250kHz.
[0010] By adopting the above technical solution, ultrasonic assistance can promote the penetration of ammonium sulfate solution, the contact with the recycled material, and the movement and exchange of ions, etc., which is beneficial to the purification step and improves the removal rate of potassium and arsenic.
[0011] Preferably, the denitration catalyst is mixed with a reinforcing agent after regeneration, the reinforcing agent comprises graphene oxide and carbon nanotubes, and the added amount of the reinforcing agent is 0.8-1.6 wt % of the denitration catalyst.
[0012] By adopting the above technical scheme, the denitrification catalyst is mixed with the enhancer after regeneration, and the graphene oxide and carbon nanotubes are composited and mixed with the denitrification catalyst, which is beneficial to increase the specific surface area, active sites and physical structure stability of the denitrification catalyst, thereby improving the catalyst activity and structural stability.
[0013] Preferably, in the reinforcing agent, the mass ratio of graphene oxide to carbon nanotubes is (0.95-1.21):(2.31-2.82).
[0014] By adopting the above technical solution and controlling the mass ratio of graphene oxide and carbon nanotubes, the two can cooperate with each other and be evenly dispersed, thereby improving the physical and chemical stability of the denitration catalyst.
[0015] Preferably, the graphene oxide is subjected to the following treatment: ultrasonically dispersing the graphene oxide in a mixture of ethanol and water, adding a 10wt% ammonia solution, stirring evenly, adding tetraethoxysilane, stirring for 23-24h, vacuum filtering, washing with ethanol, and vacuum drying at 55-60°C for 5-5.5h to obtain modified graphene oxide.
[0016] By adopting the above technical scheme, nano-silicon dioxide is hydrolyzed and deposited on the surface of graphene oxide by in-situ hydrolysis method, which can effectively improve the mechanical strength of graphene oxide, thereby effectively improving the strength of the mixed denitration catalyst and reducing the loss of the denitration catalyst during use. Graphene oxide can reduce the pulverization phenomenon of the denitration catalyst during use, which is beneficial to improving the catalytic activity and structural stability of the denitration catalyst.
[0017] Preferably, the graphene oxide is further subjected to the following treatment before ultrasonic dispersion: adding graphene oxide and tannic acid to water, ultrasonically bathing at 25° C. for 30-35 min, standing to collect the supernatant, centrifuging, and drying.
[0018] By adopting the above technical solution and using tannic acid to modify graphene oxide, the dispersibility of graphene oxide in the solution can be improved, which is beneficial to the uniformity of silicon dioxide deposition. At the same time, the hydroxyl content on the surface of graphene oxide is increased, thereby improving the catalytic activity of the denitrification catalyst.
[0019] Preferably, the carbon nanotubes are treated as follows: the carbon nanotubes are dispersed in a mixture of concentrated sulfuric acid and concentrated nitric acid, subjected to ultrasonic treatment for 25-30 minutes, subjected to thermal reflux reaction at 130-140° C. for 60-70 minutes, filtered, washed, and dried to obtain hydroxylated carbon nanotubes; The hydroxylated carbon nanotubes were placed in N,N-dimethylformamide, and ultrasonically dispersed for 30 minutes, and a mixed solution of dicyclohexylcarbodiimide, 4-dimethylaminopyridine, acrylic acid and N,N-dimethylformamide was added, and an inert gas was introduced, and the mixture was reacted at 80-85°C for 23-24 hours, and the carboxylated carbon nanotubes were obtained after washing, filtering and drying. The carboxylated carbon nanotubes were dispersed in N,N-dimethylformamide, ultrasonicated for 25-30 minutes, polyethylene polyamine was added, and an inert gas was introduced to react for 24 hours to obtain the amino carbon nanotubes.
[0020] By adopting the above technical solution to prepare amino carbon nanotubes, the bonding degree between carbon nanotubes and graphene oxide can be improved, which is beneficial to enhancing the structural stability of the denitration catalyst. At the same time, the increase in amino content can enhance the catalytic activity of the denitration catalyst.
[0021] Preferably, the mass ratio of the carboxylated carbon nanotubes to polyethylene polyamine is (0.95-1.12):(1.89-2.21).
[0022] By adopting the above technical solution and controlling the mass ratio of carboxylated carbon nanotubes to polyethylene polyamine, the degree of amination of the carbon nanotubes can be regulated. If the degree of amination is too high, the active sites will be too dense, which will reduce the catalytic efficiency.
[0023] In summary, this application has the following beneficial effects: 1. The present application physically crushes the denitration catalyst, which is beneficial to increase the contact area between the denitration catalyst and the solution in the subsequent treatment process, thereby removing impurities and potassium and arsenic on the surface of the denitration catalyst. Soaking in a hydrochloric acid solution can preliminarily remove impurities on the surface of the denitration catalyst, which is beneficial to the contact between the denitration catalyst and the ammonium sulfate solution. Soaking in an ammonium sulfate solution can effectively remove potassium and arsenic in the denitration catalyst. The purified catalyst is activated by high-temperature calcination, so that the catalytic activity of the catalyst is restored.
[0024] 2. In the present application, the denitration catalyst is regenerated and mixed with an enhancer, and graphene oxide and carbon nanotubes are composited and mixed with the denitration catalyst, which is beneficial to increase the specific surface area, active sites and physical structure stability of the denitration catalyst, thereby improving the catalyst activity and structural stability.
[0025] 3. The present application uses an in-situ hydrolysis method to hydrolyze and deposit nano-silicon dioxide on the surface of graphene oxide, which can effectively improve the mechanical strength of graphene oxide, thereby effectively improving the strength of the mixed denitration catalyst and reducing the loss of the denitration catalyst during use. Graphene oxide can also reduce the pulverization phenomenon of the denitration catalyst during use, which is beneficial to improving the catalytic activity and structural stability of the denitration catalyst. DETAILED DESCRIPTION
[0026] The present application is further described in detail below with reference to the embodiments.
[0027] Preparation Examples 1-4 of Modified Graphene Oxide Preparation Example 1 0.3 g of graphene oxide was ultrasonically dispersed in a mixture of 76 mL of ethanol and 3 mL of water, 5.3 mL of 10 wt% ammonia solution was added, and 2.8 mL of tetraethoxysilane was added after stirring evenly. After stirring for 23 h, vacuum filtration and ethanol washing were performed, and vacuum drying was performed at 55 ° C for 5.5 h to obtain modified graphene oxide.
[0028] Preparation Example 2 0.3 g of graphene oxide was ultrasonically dispersed in a mixture of 84 mL of ethanol and 3.5 mL of water, 5.7 mL of 10 wt% ammonia solution was added, and 3.2 mL of tetraethoxysilane was added after stirring evenly. After stirring for 24 h, vacuum filtration, ethanol washing, and vacuum drying at 60 ° C for 5 h to obtain modified graphene oxide.
[0029] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the graphene oxide is further treated as follows before ultrasonic dispersion: 2 mg of graphene oxide and 1.5 mg of tannic acid are added to 25 mL of water, ultrasonically bathed at 25° C. for 30 min, allowed to stand, the supernatant is taken, centrifuged, and dried.
[0030] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the graphene oxide is further treated as follows before ultrasonic dispersion: 2.2 mg of graphene oxide and 1.8 mg of tannic acid are added to 28 mL of water, ultrasonically bathed at 25°C for 35 min, allowed to stand, the supernatant is taken, centrifuged, and dried.
[0031] Preparation Example 5-8 of Aminated Carbon Nanotubes Preparation Example 5 0.9 g of carbon nanotubes were dispersed in a mixture of 18 mL of concentrated sulfuric acid and 21 mL of concentrated nitric acid, and subjected to ultrasonic treatment for 25 min, followed by a heat reflux reaction at 140°C for 60 min, and then filtered, washed, and dried to obtain hydroxylated carbon nanotubes. 46 mg of hydroxylated carbon nanotubes were placed in 40 mL of N,N-dimethylformamide, and ultrasonically dispersed for 30 min. A mixed solution of 0.19 g of dicyclohexylcarbodiimide, 0.014 g of 4-dimethylaminopyridine, 0.49 g of acrylic acid and 40 mL of N,N-dimethylformamide was added, and an inert gas was introduced. The mixture was reacted at 80°C for 24 h, and the carboxylated carbon nanotubes were obtained after washing, filtering and drying. 0.2 g of carboxylated carbon nanotubes were dispersed in 50 mL of N,N-dimethylformamide, ultrasonicated for 25 min, polyethylene polyamine was added, the mass ratio of carboxylated carbon nanotubes to polyethylene polyamine was 0.95:1.89, inert gas was introduced to react for 24 h, and amino carbon nanotubes were obtained.
[0032] Preparation Example 6 1.2 g of carbon nanotubes were dispersed in a mixture of 23 mL of concentrated sulfuric acid and 22 mL of concentrated nitric acid, and subjected to ultrasonic treatment for 30 min, followed by reflux reaction at 130°C for 70 min, and then filtered, washed, and dried to obtain hydroxylated carbon nanotubes. 55 mg of hydroxylated carbon nanotubes were placed in 45 mL of N,N-dimethylformamide, and ultrasonically dispersed for 30 min. A mixed solution of 0.23 g of dicyclohexylcarbodiimide, 0.017 g of 4-dimethylaminopyridine, 0.6 g of acrylic acid and 45 mL of N,N-dimethylformamide was added, and an inert gas was introduced. The mixture was reacted at 85°C for 23 h, and the carboxylated carbon nanotubes were obtained after washing, filtering and drying. 0.21 g of carboxylated carbon nanotubes were dispersed in 55 mL of N,N-dimethylformamide, and ultrasonicated for 30 min. Polyethylene polyamine was added, and the mass ratio of carboxylated carbon nanotubes to polyethylene polyamine was 1.12:2.21. Inert gas was introduced to react for 24 h to obtain amino carbon nanotubes.
[0033] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 5 is that in Preparation Example 7, the mass ratio of carboxylated carbon nanotubes to polyethylene polyamine is 0.95:1.25.
[0034] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 5 is that in Preparation Example 8, the mass ratio of carboxylated carbon nanotubes to polyethylene polyamine is 0.95:2.51. Example
[0035] Example 1 A method for recycling denitration catalyst recovery material comprises the following steps: (1) Pretreatment: crush the denitration catalyst recovery material and pass it through a 16-mesh sieve; (2) Cleaning: Soak the powder in 8% hydrochloric acid solution for 11 h, and rinse with water until neutral; (3) Purification: The cleaned recycled material is placed in a rotary reactor, an 8% ammonium sulfate solution is added, the reaction temperature is controlled at 70°C, the stirring speed is 190 rpm, and the reaction is continued for 2 hours; (4) Regeneration: The purified recycled material is dried and then calcined at 500°C for 4 hours in an inert gas atmosphere.
[0036] Example 2 A method for recycling denitration catalyst recovery material comprises the following steps: (1) Pretreatment: crush the denitration catalyst recovery material and pass it through a 16-mesh sieve; (2) Cleaning: Soak the powder in 4% hydrochloric acid solution for 12 h, and rinse with water until neutral; (3) Purification: The cleaned recycled material was placed in a rotary reactor, and a 12% ammonium sulfate solution was added. The reaction temperature was controlled at 60°C and the stirring speed was 210 rpm for 2.2 h. (4) Regeneration: The purified recycled material is dried and then calcined at 600°C in an inert gas atmosphere for 3.5 hours.
[0037] Example 3 The difference between Example 3 and Example 1 is that in Example 3, the concentration of hydrochloric acid is 5wt%, the concentration of sodium sulfate solution is 10wt%, the calcination temperature is 550°C, and the duration is 3.5h.
[0038] Example 4 The difference between Example 4 and Example 1 is that in Example 4, ultrasonic assisted treatment is used in the purification step, and the ultrasonic frequency is 240 kHz.
[0039] Example 5 The difference between Example 5 and Example 1 is that in Example 5, ultrasonic assisted treatment is used in the purification step, and the ultrasonic frequency is 250 kHz.
[0040] Example 6 The difference between Example 6 and Example 1 is that in Example 6, the denitration catalyst is mixed with an enhancer after regeneration, the enhancer includes graphene oxide and carbon nanotubes, the amount of the enhancer added is 0.8wt% of the denitration catalyst, and the mass ratio of graphene oxide to carbon nanotubes is 0.95:2.31.
[0041] Example 7 The difference between Example 7 and Example 1 is that in Example 7, the denitration catalyst is mixed with an enhancer after regeneration, the enhancer includes graphene oxide and carbon nanotubes, the amount of the enhancer added is 1.6wt% of the denitration catalyst, and the mass ratio of graphene oxide to carbon nanotubes is 1.21:2.82.
[0042] Example 8 The difference between Example 8 and Example 6 is that in Example 8, the amount of the enhancer added is 0.4 wt % of the denitration catalyst.
[0043] Example 9 The difference between Example 9 and Example 6 is that in Example 9, the amount of the enhancer added is 2.3 wt % of the denitration catalyst.
[0044] Example 10 The difference between Example 10 and Example 6 is that in Example 10, the mass ratio of graphene oxide to carbon nanotubes is 0.95:1.98.
[0045] Embodiment 11 The difference between Example 11 and Example 6 is that in Example 11, the mass ratio of graphene oxide to carbon nanotubes is 0.95:3.13.
[0046] Example 12 The difference between Example 12 and Example 6 is that in Example 12, an equal amount of modified graphene oxide is used instead of graphene oxide, and the modified graphene oxide is the modified graphene prepared in Preparation Example 1.
[0047] Embodiment 13 The difference between Example 13 and Example 6 is that in Example 13, an equal amount of modified graphene oxide is used instead of graphene oxide, and the modified graphene oxide is the modified graphene prepared in Preparation Example 2.
[0048] Embodiment 14 The difference between Example 14 and Example 6 is that in Example 14, an equal amount of modified graphene oxide is used instead of graphene oxide, and the modified graphene oxide is the modified graphene prepared in Preparation Example 3.
[0049] Embodiment 15 The difference between Example 15 and Example 6 is that in Example 15, an equal amount of modified graphene oxide is used instead of graphene oxide, and the modified graphene oxide is the modified graphene prepared in Preparation Example 4.
[0050] Example 16 The difference between Example 16 and Example 6 is that in Example 16, an equal amount of amino-modified carbon nanotubes are used to replace carbon nanotubes, and the amino-modified carbon nanotubes are the amino-modified carbon nanotubes prepared in Preparation Example 5.
[0051] Embodiment 17 The difference between Example 17 and Example 6 is that in Example 17, an equal amount of amino-modified carbon nanotubes are used to replace carbon nanotubes, and the amino-modified carbon nanotubes are the amino-modified carbon nanotubes prepared in Preparation Example 6.
[0052] Embodiment 18 The difference between Example 18 and Example 6 is that in Example 18, an equal amount of amino-modified carbon nanotubes are used to replace carbon nanotubes, and the amino-modified carbon nanotubes are the amino-modified carbon nanotubes prepared in Preparation Example 7.
[0053] Embodiment 19 The difference between Example 19 and Example 6 is that in Example 19, an equal amount of amino-modified carbon nanotubes are used to replace carbon nanotubes, and the amino-modified carbon nanotubes are the amino-modified carbon nanotubes prepared in Preparation Example 8.
[0054] Performance testing Catalytic activity test of catalyst: Use simulated flue gas to test the denitrification of catalyst. The simulated flue gas composition is: NO: 550ppm, NH3: 520ppm, O2: 5%, N2 as balance gas, and the air velocity is 28000h -1 , the flue gas flow rate is 300mL / min, the same volume of catalyst is taken and placed in the fixed bed reactor for testing, the reaction temperature is controlled to be 250℃, the regenerated denitration catalyst is tested together with the new catalyst of the same model, the reaction activities of the two are recorded, and the ratio of the reaction activities of the regenerated denitration catalyst to the new catalyst is calculated, recorded as the activity recovery rate, and the results are recorded in Table 1.
[0055] Catalyst wear rate test: According to the test method for the wear rate of honeycomb flue gas denitrification catalyst (GB / T31587-2015), the gas velocity in the catalyst channel is 14.5m / s, the abrasive is dry 0.300mm high hardness quartz sand, and the abrasive concentration is 50g / m 3 , flushing time 2h, weigh the mass of the denitration catalyst before and after detection, and calculate the wear mass, and record it in Table 1.
[0056] The mass percentages of potassium and arsenic in the regenerated denitration catalyst were determined and recorded in Table 1.
[0057] Table 1 Performance test of denitrification catalyst after regeneration According to Examples 1-3 and Table 2, it can be seen that Examples 1-3 have a higher activity recovery rate and less wear mass, the potassium and arsenic contents in the denitration catalyst are lower, the regenerated denitration catalyst has a better impurity removal effect, the activity recovery is good, and it can continue to be put into use, and the catalytic efficiency is better. After the denitration catalyst is physically crushed, the contact area with the liquid is increased. The impurities on the surface of the denitration catalyst can be removed by soaking in a hydrochloric acid solution, which is beneficial to the contact between the denitration catalyst and the ammonium sulfate solution. The ammonium sulfate solution can react with the potassium and arsenic in the denitration catalyst to remove the potassium and arsenic in the denitration catalyst and reduce their contents. The catalyst activity can be activated by high-temperature calcination, thereby restoring the catalytic activity of the regenerated denitration catalyst.
[0058] Compared with Example 1, the potassium and arsenic content of Example 4-5 is reduced. Ultrasonic-assisted purification treatment is used in Example 4-5, which shows that ultrasonic-assisted purification treatment can effectively increase the reaction rate of potassium and arsenic in the denitration catalyst with ammonium sulfate solution. Ultrasonic assistance can promote the penetration of ammonium sulfate solution, increase the contact between ammonium sulfate solution and recycled materials, and the mobile exchange of solution ions, which is beneficial to the reaction of ammonium sulfate solution with the denitration catalyst, increase the reaction rate, promote the reaction process, and thus improve the removal rate of potassium and arsenic.
[0059] Compared with Example 1, the activity recovery rate of Example 6-7 is improved and the wear quality is reduced. In Example 6-7, the regenerated denitration catalyst is mixed with an enhancer, and the enhancer includes graphene oxide and carbon nanotubes. Both graphene oxide and carbon nanotubes have good mechanical properties and a large specific surface area. Graphene oxide and carbon nanotubes are compounded to form a enhancer, which is compounded with the denitration catalyst, which is beneficial to increase the specific surface area, active sites and physical structure stability of the denitration catalyst. Graphene oxide can reduce the pulverization phenomenon of the denitration catalyst during use, and effectively improves the catalyst activity and the structural stability of the catalyst.
[0060] Compared with Example 6, the activity recovery rate of Example 8-9 is decreased, and the wear quality is improved. Example 8-9 changes the amount of the reinforcing agent added, which shows that the amount of the reinforcing agent added affects the activity and strength of the deNOx catalyst. The reduction in the amount of the reinforcing agent added weakens its reinforcing effect on the deNOx catalyst. When the amount of the reinforcing agent added increases, graphene oxide and carbon nanotubes are prone to agglomeration and uneven distribution, thereby affecting the activity and strength of the deNOx catalyst.
[0061] Compared with Example 6, the activity recovery rate of Example 10-11 is decreased, and the wear quality is improved. Example 10-11 changes the mass ratio of graphene oxide to carbon nanotubes in the enhancer, indicating that there is a synergistic effect between graphene oxide and carbon nanotubes. Changing the mass ratio of graphene oxide and carbon nanotubes reduces the enhancement effect of the two on the denitration catalyst, thereby reducing the activity and strength of the denitration catalyst.
[0062] Compared with Example 6, the wear quality of Example 12-13 is reduced. Example 12-13 uses modified graphene oxide instead of graphene oxide. The graphene oxide is hydrolyzed and precipitated by tetraethoxysilane, and nano-silicon dioxide is deposited on the surface of the graphene oxide, which can effectively improve the mechanical strength of the graphene oxide, thereby effectively improving the strength of the denitrification catalyst and reducing wear.
[0063] Compared with Example 12, the activity recovery rate of Example 14-15 is improved, and the wear quality is reduced. The modified graphene oxide used in Example 14-15 is modified with tannic acid before being treated with tetraethoxysilane. After the graphene oxide is modified with tannic acid, the surface properties of the graphene oxide can be improved, the dispersibility of the graphene oxide in the solution is improved, and the uniformity of the silicon dioxide deposition is facilitated. At the same time, the hydroxyl content on the surface of the graphene oxide is increased, more active sites are provided, and the catalytic activity of the denitrification catalyst is improved.
[0064] Compared with Example 6, the activity recovery rate of Example 16-17 is improved and the wear quality is reduced. Example 16-17 uses amino carbon nanotubes instead of carbon nanotubes. The carbon nanotubes are treated with amino to increase the surface amino groups, which is beneficial to improve the bonding degree between the carbon nanotubes and graphene oxide, thereby increasing the composite effect of the two, thereby improving the structural stability of the denitration catalyst. At the same time, the amino treatment can increase the active sites of the carbon nanotubes, thereby improving the catalytic activity of the denitration catalyst.
[0065] Compared with Example 16, the activity recovery rate of Example 18-19 is decreased. During the preparation of the amino carbon nanotubes used in Example 18-19, the mass ratio of carboxylated carbon nanotubes to polyethylene polyamine was changed. The mass ratio of carboxylated carbon nanotubes to polyethylene polyamine affected the degree of amination of the carbon nanotubes. Too high or too low an amino content will affect the catalytic activity of the denitration catalyst.
[0066] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for recycling denitration catalyst recovery material, characterized in that: The following steps are involved: (1) Pretreatment: crush the denitration catalyst recovery material and pass it through a 16-mesh sieve; (2) Cleaning: Soak the powder in a 4-8% hydrochloric acid solution for 11-12 hours, and rinse with water until neutral; (3) Purification: Place the cleaned recycled material in a rotary reactor, add 8-12% ammonium sulfate solution by mass, control the reaction temperature at 60-70°C, stir at 190-210 rpm, and continue for 2-2.2 hours; (4) Regeneration: The purified recycled material is dried and then calcined at 500-600°C in an inert gas atmosphere for 3.5-4 hours.
2. A method for recycling denitration catalyst recovery materials according to claim 1, characterized in that: The concentration of the hydrochloric acid solution is 5wt%, the concentration of the sodium sulfate solution is 10wt%, the calcination temperature is 550°C, and the duration is 3.5h.
3. A method for recycling denitration catalyst recovery materials according to claim 1, characterized in that: In the purification step, ultrasonic wave is used to assist the treatment, and the ultrasonic wave frequency is 240-250 kHz.
4. A method for recycling denitration catalyst recovery material according to claim 1, characterized in that: The denitration catalyst is regenerated and mixed with a reinforcing agent, the reinforcing agent includes graphene oxide and carbon nanotubes, and the added amount of the reinforcing agent is 0.8-1.6wt% of the denitration catalyst.
5. A method for recycling denitration catalyst recovery material according to claim 4, characterized in that: In the reinforcing agent, the mass ratio of graphene oxide to carbon nanotubes is (0.95-1.21):(2.31-2.82).
6. A method for recycling denitration catalyst recovery material according to claim 4, characterized in that: The graphene oxide is subjected to the following treatments: the graphene oxide is ultrasonically dispersed in a mixture of ethanol and water, a 10wt% ammonia solution is added, tetraethoxysilane is added after stirring evenly, the mixture is stirred for 23-24 hours, vacuum filtered, washed with ethanol, and vacuum dried at 55-60° C. for 5-5.5 hours to obtain modified graphene oxide.
7. A method for recycling denitration catalyst recovery materials according to claim 6, characterized in that: The graphene oxide is also subjected to the following treatment before ultrasonic dispersion: adding graphene oxide and tannic acid to water, ultrasonically bathing at 25° C. for 30-35 minutes, standing to collect the supernatant, centrifuging, and drying.
8. A method for recycling denitration catalyst recovery material according to claim 4, characterized in that: The carbon nanotubes are treated as follows: the carbon nanotubes are dispersed in a mixture of concentrated sulfuric acid and concentrated nitric acid, subjected to ultrasonic treatment for 25-30 minutes, subjected to thermal reflux reaction at 130-140° C. for 60-70 minutes, filtered, washed, and dried to obtain hydroxylated carbon nanotubes; The hydroxylated carbon nanotubes were placed in N,N-dimethylformamide, and ultrasonically dispersed for 30 minutes, and a mixed solution of dicyclohexylcarbodiimide, 4-dimethylaminopyridine, acrylic acid and N,N-dimethylformamide was added, and an inert gas was introduced, and the mixture was reacted at 80-85°C for 23-24 hours, and the carboxylated carbon nanotubes were obtained after washing, filtering and drying. The carboxylated carbon nanotubes were dispersed in N,N-dimethylformamide, ultrasonicated for 25-30 minutes, polyethylene polyamine was added, and an inert gas was introduced to react for 24 hours to obtain the amino carbon nanotubes.
9. A method for recycling denitration catalyst recovery material according to claim 8, characterized in that: The mass ratio of the carboxylated carbon nanotubes to polyethylene polyamine is (0.95-1.12):(1.89-2.21).